(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The emergence of the Covid-19 virus and its catastrophic health, economic and social effects have created many unprecedented challenges for the countries of the world and international organizations.One of the important challenges posed by this pandemic is the issue of intellectual property rights under the World Trade Organization Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and reconciling its provisions with the right to equitable access to Covid-19 vaccines. Where the rich countries of the world and behind them the vaccine manufacturers adhere to the strict application of the provisions of the agreement, while the developing and poor countries suffer and demand justice for their populations to obtain adequate doses of the vaccine.This research aims to shed light on the issue of equitable access and its importance for all countries of the world and how the TRIPS Agreement affects the achievement of equitable access and to study the problems raised by the TRIPS Agreement in this issue, and then to discuss the various trends that have emerged in order to reconcile between equitable access and ensuring respect for the provisions of the Agreement TRIPS will study the advantages and disadvantages of each of these trends and present proposals that can contribute to reconciling the provisions of the Convention and ensuring the right to equitable access to the vaccine.